Time decay estimates for wave equations with transmission and boundary conditions - Mihalinčić, Krešo (Array, 2019)
Time decay estimates are derived for solutions of some initial value problems of wave propagation, based on the method of stationary phase. Solutions to three dimensional wave equation in wedges and one dimensional wave equation with a constant potential are shown to decay like t-1 and t-1/2, respectively. Dependencies of the results on initial data and physical implications are discussed.